2018
DOI: 10.1002/2017ja024874
|View full text |Cite
|
Sign up to set email alerts
|

Control of ULF Wave Accessibility to the Inner Magnetosphere by the Convection of Plasma Density

Abstract: During periods of storm activity and enhanced convection, the plasma density in the afternoon sector of the magnetosphere is highly dynamic due to the development of plasmaspheric drainage plume (PDP) structure. This significantly affects the local Alfvén speed and alters the propagation of ULF waves launched from the magnetopause. Therefore, it can be expected that the accessibility of ULF wave power for radiation belt energization is sensitively dependent on the recent history of magnetospheric convection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 65 publications
7
84
1
Order By: Relevance
“…It is evident that the FLRs in Figure cannot be interpreted with the usual 2‐D toroidal FLR theory. The 3‐D nature of the equilibrium requires a theoretical description that is somewhat different to 2‐D (Degeling et al, ; Wright & Elsden, ). Recall that Elsden and Wright () showed that the frequency of Alfvén waves on a given ridge is the same everywhere along the ridge.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…It is evident that the FLRs in Figure cannot be interpreted with the usual 2‐D toroidal FLR theory. The 3‐D nature of the equilibrium requires a theoretical description that is somewhat different to 2‐D (Degeling et al, ; Wright & Elsden, ). Recall that Elsden and Wright () showed that the frequency of Alfvén waves on a given ridge is the same everywhere along the ridge.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…These equations, along with equation for b 1 μ , form a closed set (along with appropriate boundary conditions) and have been analyzed and modeled by many authors over the last four decades (Allan & Knox, ; Allan & Poulter, ; Degeling & Rankin, ; Degeling et al, , ; Hasegawa & Chen, ; Lee, ; Lee & Lysak, ; Lysak et al, ; Rankin et al, ; Walker, ). The formalism for the wave model presented here is an extension of the approach taken by Rankin and coauthors in a number of previous works (Frycz et al, ; Rankin et al, , ; Wang et al, ).…”
Section: Analytic Model Formulationmentioning
confidence: 99%
“…Understanding the structure of the fast mode which develops in an asymmetric equilibrium about noon has been used recently to explain the dawn‐dusk asymmetry of Pc5 wave observations (Wright et al, ). Further, the inclusion of azimuthal magnetic and density asymmetries has also been used to consider the effect of a plasmaspheric plume on ULF wave propagation (Degeling et al, ). A key aspect of the current work is considering the excitation of FLRs in 3‐D (Elsden & Wright, , ; Wright & Elsden, ), where resonances can exist at any given polarization angle between toroidal and poloidal.…”
Section: Introductionmentioning
confidence: 99%